2021
DOI: 10.1021/acscatal.1c03875
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of 2H-Azirines by Asymmetric Allylation Reactions

Abstract: A practical and efficient method for kinetic resolution of azirines has been achieved via asymmetric allylations of racemic 2H-azirines with boron allylation reagents enabled by Bi­(OAc)3/chiral phosphoric acid catalysis. A broad range of azirine substrates with electron-withdrawing and electron-donating groups at the two aromatic rings, as well as the different allyl boron reagents, were well tolerated in this methodology, providing high kinetic resolution performance (with an s-factor of up to 127) under ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…2 H -Azirines, as easily accessible building blocks, have been actively employed for an easy increase of the molecular complexity. 37–43 Owing to the intrinsic strain, 2 H -azirines can undergo a facile ring opening, and thus function as C–C–N or C–N–C triatomic synthons. In turn, ynamides are customizable, highly reactive alkynes, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…2 H -Azirines, as easily accessible building blocks, have been actively employed for an easy increase of the molecular complexity. 37–43 Owing to the intrinsic strain, 2 H -azirines can undergo a facile ring opening, and thus function as C–C–N or C–N–C triatomic synthons. In turn, ynamides are customizable, highly reactive alkynes, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The developed protocol was applied to the synthesis of (+)‐AG‐041R as a gastrin receptor antagonist, and the total synthesis of (−)‐psychotriasine as naturally occurring bioactive molecules. The same group also reported the highly enantioselective allylation of azirins from a racemic mixture of (2 H )‐azirines 89 using the same catalytic system (Scheme 21b) [72] . As described by the authors, the Bi‐CPA catalyst first bound to the allyl species 86 which then reacted with the racemic azirins at different rates resulting in excellent kinetic resolution ( s ‐factor of up to 127).…”
Section: Enantioselective Reactions Using P‐block Elementsmentioning
confidence: 88%
“…The same group also reported the highly enantioselective allylation of azirins from a racemic mixture of (2H)-azirines 89 using the same catalytic system (Scheme 21b). [72] As described by the authors, the Bi-CPA catalyst first bound to the allyl species 86 which then reacted with the racemic azirins at different rates resulting in excellent kinetic resolution (s-factor of up to 127).…”
Section: Bismuth Catalysis Using Chiral Phosphoric Acidsmentioning
confidence: 99%
“…According to our previous work, 19,20 a plausible mechanistic pathway was rationalized as outlined in Scheme 5a. First, an anion exchange between CPA ( S )- 6c and Bi(OAc) 3 occurs beforehand to form the chiral phosphate diacetate Bi( iii ) as the active catalytic species.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
“…17 Since fluorine has unique and excellent properties, 2 it is very meaningful to introduce fluorine atoms into the dibenzo[ b,f ][1,4]oxazepine framework. Recently, we have developed a Bi(OAc) 3 /chiral phosphoric acid (CPA) 18 catalytic system, which was successfully applied in the asymmetric allylation of the CX (X = N or O) bond 19 and the asymmetric Friedel–Crafts alkylation of phenols. 20 We found that chiral bismuth phosphate catalysts have some unique advantages (Scheme 2c).…”
Section: Introductionmentioning
confidence: 99%